End‐user oriented public‐private partnerships in real estate industry - Majamaa, Wisa; Junnila, Seppo; Doloi, Hemanta; Niemostö, Emma (International Journal of Strategic Property Management, 2010)
The European Union (EU) is reforming its public services and suggesting Public‐Private Partnerships (PPPs) as a solution for producing high quality and cost effective real estate service delivery. However, the use of PPP approach in real estate industries has been found to have significant constraints related to the end‐users’ (general public’s) perspective. The purpose of the paper is to show how PPP projects have failed to produce desirable characteristics expressed in purchasing processes and fulfilment of the end‐user expectations. While the customer‐oriented development of public services and the needs of the end‐users were noted to be crucial points in all five major Finnish PPP projects studied, the case studies pointed out a fundamental lack of understanding and maintaining the end‐user perspective through the tendering and evaluation processes. Especially, in the final stage of evaluation, and evaluation criteria used to decision making, the disappearance of the end‐users’ perspective was evident. The findings are further used to develop a new suggested Public‐Private‐People Partnership (4P) model. The results can be useful to the public sector’s purchasers and to the private sector’s providers to understand the limitations of current PPP practices and to further develop their practices towards more customer‐oriented service production. First published online: 18 Oct 2010